The financial crisis and the European Union - Efenhoff, Klaus G. (Global economic studies series., 2009)
The European Union (EU) is a treaty-based, institutional framework that defines and manages economic and political co-operation among its 27 member states (Austria, Belgium, Bulgaria, Cyprus, the Czech Republic, Denmark, Estonia, Finland, France, Germany, Greece, Hungary, Ireland, Italy, Latvia, Lithuania, Luxembourg, Malta, the Netherlands, Poland, Portugal, Romania, Slovakia, Slovenia, Spain, Sweden and the United Kingdom). The Union is the latest stage in a process of European integration begun after World War II to promote peace and economic prosperity in Europe. Its founders hoped that by creating communities of shared sovereignty, another war in Europe would be unthinkable. Since the 1950's, this European integration project has expanded to encompass other economic sectors, a customs union, a single market in which goods, people, and capital move freely, a common agricultural policy, and a common currency (the Euro). The global financial crisis has hit the EU hard. The latest economic forecasts painted a bleak picture of close to zero growth and risks of contraction for the EU economy in 2009, with unemployment rising by some 2.7 million in the next two years, on the assumption that no corrective action is taken. Quick and decisive action is needed to stop this downward spiral. The interplay of national and EU action can help all Member States weather the worst of the global economic storms and emerge stronger from the crisis.